2016
DOI: 10.18869/acadpub.jhs.4.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carson Trophic Index in Dam Lake: a Case Study of Ekbatan Dam

Abstract: Background and purpose: The study aimed to investigate the trophic state of Ekbatan Dam Lake. In the current research, the quality of water behind the dam was studied during the months July and January in order to compare the trophic state and zonation of the reservoir in two different seasons (dry and wet). Materials and Methods: 15 stations were selected in different points of Ekbatan Dam Lake and sampling was accomplished in July and January. To determine the rate of eutrophication in the reservoir, 30 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…155, 154 and 145 with 0.39, 0.21 and 0.36 mg/l, respectively. The investigation of phosphorous levels in Taham and Ghalharod Rivers using GIS system showed that 15% of the studied stations had levels higher than acceptable levels set by EPA [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…155, 154 and 145 with 0.39, 0.21 and 0.36 mg/l, respectively. The investigation of phosphorous levels in Taham and Ghalharod Rivers using GIS system showed that 15% of the studied stations had levels higher than acceptable levels set by EPA [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The Trophic State Index (CTSI), set up via Carlson in 1977 [9], is ordinarily utilized by water the board offices and associations throughout the planet. The CTSI is a typical and valuable water quality record that has been utilized as the essential measurement in numerous examinations [10][11]. CTSI is determined utilizing three separate water quality variables: chlorophyll-a (Chl-a) fixation, total phosphorus (TP) focus, and Secchi depth (SD).…”
Section: Introductionmentioning
confidence: 99%